The Implementation of Scratch Application-Based Learning Media for Food and Beverage Service - Ramadhanty, Nayla Insyira; Mulyati, Mulyati; Faesal, Muhammad (Politeknik Pariwisata Lombok, 2026)
Introduction: Quality education supports national development by fostering knowledge and skills. Based on observations at SMK Negeri 33 Jakarta, limited variation in instructional media was identified in the Food and Beverage Service subject. To address this issue, interactive learning media on glassware types and functions was developed using Scratch to enhance student engagement and learning outcomes. Methodology: This study employed a Research and Development (R&D) approach using the ADDIE model involving 60 eleventh-grade hospitality students. The research focused on feasibility validation through expert review and student trials using a five-point Likert-scale questionnaire. Findings: The Scratch-based media obtained feasibility scores ranging from 88% to 96%, categorized as “Very Feasible” across expert validation, one-to-one trials, small group testing, and field testing. Conclusion: The developed media is suitable for classroom implementation and provides an interactive alternative to conventional instruction in vocational hospitality education.